1999
DOI: 10.1074/jbc.274.7.4027
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Exocytosis by Cyclin-dependent Kinase 5 via Phosphorylation of Munc18

Abstract: Munc18a, a mammalian neuronal homologue of Saccharomyces cerevisiae Sec1p protein, is essential for secretion, likely as a result of its high affinity interaction with the target SNARE protein syntaxin 1a (where SNARE is derived from SNAP receptor (the soluble Nethylmaleimide-sensitive fusion protein)). However, this interaction inhibits vesicle SNARE interactions with syntaxin that are required for secretory vesicles to achieve competency for membrane fusion. As such, regulation of the interaction between Mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
154
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 53 publications
5
154
0
5
Order By: Relevance
“…There were no significant differences in mean dendritic length in any of the experimental conditions; this indicates that the observed changes in spine density do not result from dendritic lengthening or shortening. Together, these data demonstrate that the ability of chronic cocaine to increase NAc spine density is dependent on the activity of Cdk5.Previous studies have demonstrated that Cdk5 co-localizes with presynaptic proteins involved in exocytosis and synaptic transmission (Shuang et al, 1998;Fletcher et al, 1999) as well as post-synaptic D1 receptor-mediated second messenger cascades (Bibb et al, 1999a). Cdk5 co-localizes with DARPP-32 (Dopamine and cyclic AMP [cAMP] Regulated Phosphoprotein, Mr 32 kDa) in cell bodies and dendritic shafts in NAc (Bibb et al, 2001).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…There were no significant differences in mean dendritic length in any of the experimental conditions; this indicates that the observed changes in spine density do not result from dendritic lengthening or shortening. Together, these data demonstrate that the ability of chronic cocaine to increase NAc spine density is dependent on the activity of Cdk5.Previous studies have demonstrated that Cdk5 co-localizes with presynaptic proteins involved in exocytosis and synaptic transmission (Shuang et al, 1998;Fletcher et al, 1999) as well as post-synaptic D1 receptor-mediated second messenger cascades (Bibb et al, 1999a). Cdk5 co-localizes with DARPP-32 (Dopamine and cyclic AMP [cAMP] Regulated Phosphoprotein, Mr 32 kDa) in cell bodies and dendritic shafts in NAc (Bibb et al, 2001).…”
supporting
confidence: 58%
“…Previous studies have demonstrated that Cdk5 co-localizes with presynaptic proteins involved in exocytosis and synaptic transmission (Shuang et al, 1998;Fletcher et al, 1999) as well as post-synaptic D1 receptor-mediated second messenger cascades (Bibb et al, 1999a). Cdk5 co-localizes with DARPP-32 (Dopamine and cyclic AMP [cAMP] Regulated Phosphoprotein, Mr 32 kDa) in cell bodies and dendritic shafts in NAc (Bibb et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cdk5 has been suggested as contributing to the control of neuronal positioning in Reelin signaling during neural development (5) and to mediate neuronal guidance by regulating semaphorin-3A with Fyn kinase (6). Cdk5 and p35 have recently also been shown to regulate presynaptic and postsynaptic activity by phosphorylating Munc-18, amphiphysin, and the NR2A subunit of the N-methyl-D-aspartate receptor (7)(8)(9)(10)(11). Cdk5 activity also regulates dopamine signaling by phosphorylating DARPP-32 protein (12) and has been shown to up-regulate the expression of acetylcholine receptor at the neuromuscular junction (13).…”
mentioning
confidence: 99%
“…Phosphorylated Munc18 have shown the reduced affinity for syntaxin1A but with some difference where phosphorylation by Cdk5 resulted in a greater reduction in syntaxin1A binding affinity (Shuang et al, 1996;Fletcher et al, 1999). The phosphorylation of SV proteins may alter physiological function.…”
Section: Resultsmentioning
confidence: 99%